Perovskite-related (CH3NH3)3Sb2Br9 for forming-free memristor and low-energy-consuming neuromorphic computing. Issue 13 (20th March 2019) - Yang, June-Mo; Choi, Eun-Suk; Kim, So-Yeon; Kim, Jeong-Hoon; Park, Jin-Hong; Park, Nam-Gyu
Abstract : Perovskite-related (CH3 NH3 )3 Sb2 Br9 exhibits forming free properties in memristor devices and low energy consuming artificial synaptic behavior for neuromorphic computing. Abstract : Organic–inorganic halide perovskite materials exhibit excellent memristive properties, such as a high on/off ratio and low switching voltage. However, most studies have focused on Pb-based perovskites. Here, we report on the resistive switching and neuromorphic computing properties of Pb-free perovskite-related MA3 Sb2 Br9 (MA = CH3 NH3 ). The Ag/PMMA/MA3 Sb2 Br9 /ITO devices show forming-free characteristics due to a self-formed conducting filament induced by metallic Sb present in the as-prepared MA3 Sb2 Br9 layer. An MA3 Sb2 Br9 -based memristor exhibits a reliable on/off ratio (∼10 2 ), an endurance of 300 cycles, a retention time of ∼10 4 s and multilevel storage characteristics. Furthermore, synaptic characteristics, such as short-term potentiation, short-term depression and long-term potentiation, are revealed along with a low energy-consumption of 117.9 fJ μm −2, which indicates that MA3 Sb2 Br9 is a promising material for neuromorphic computing.